Patterns and trends in insulin initiation and intensification among patients with type 2 diabetes mellitus in the Western Pacific region. (2nd September 2018) - Jabbar, Abdul; Mohamed, Wan Mohd Izani Bin Wan; Ozaki, Risa; Mirasol, Robert; Treuer, Tamas; Lew, Thomas; Qi, Rong; Sheu, Wayne H-H; Deerochanawong, Chaicharn; Babineaux, Steven M.
Abstract: Objective: Current and future estimates of the burden of diabetes for the Western Pacific (WP) region are among the highest in the world. Verifying Insulin Strategy and Initial Health Outcome Analysis (VISION) was an 18 month observational study that explored treatment approaches in patients with type 2 diabetes mellitus (T2DM) initiating insulin in the WP region. Methods: A total of 1065 patients aged ≥18 years with T2DM initiating insulin therapy in normal clinical course were enrolled from Hong Kong, Malaysia, Philippines, Taiwan and Thailand. Participants' data was recorded by the treating physicians. Patient-reported outcomes (PROs) were assessed using questionnaires completed by participants. Results: The mean age of patients was 57.2 years with mean glycosylated hemoglobin (HbA1c) of 10.0%. About 66% of patients had an HbA1c ≥9.0% at insulin initiation despite 74% of them being on two or more oral antidiabetic agents at the time of insulin initiation. Basal insulin was initiated in 72% and premixed insulin in 27% of patients. Changes in insulin therapy was observed in 63% of patients and, by the end of study, 28% achieved HbA1c levels of <7.5%. The proportion of patients completely satisfied with their insulin treatment increased over the study course and the quality of life (QoL) score increased from baseline to the study end. Conclusion: As high HbA1C levels indicate a delayed start of insulin therapy, timely initiation and early intensification of insulin therapy is necessary in the region to achieve adequate glycemic control in time and prevent diabetes complications. Data from PROs suggests that the insulin treatment improves QoL in most patients.